Triterpenic Acid Amides as a Promising Agent for Treatment of Metabolic Syndrome - Vladislav Fomenko; Mikhail Blokhin; Sergey Kuranov; Mikhail Khvostov; Dmitriy Baev; Marina S. Borisova; Olga Luzina; Tatyana G. Tolstikova; Nariman F. Salakhutdinov (MDPI AG, 2020)
A series of triterpenic acid amides were synthesized incorporating a 2-ethoxy-3-phenylpropanoic acid pharmacophore fragment. The synthesized compounds were tested for their ability to improve glycemic control and to counter lipid abnormalities in C57BL/6 mice placed on a high-fat/high-cholesterol diet. Of all tested compounds, the dihydrobetulonic derivative (16b) had the most pronounced effect in decreasing blood glucose levels, total cholesterol (TC), and high-density lipoproteins (HDL). All the synthesized compounds displayed a relatively safe profile in the animal studies carried out in this work.